Closed-chest small animal model to study myocardial infarction in an MRI environment in real time - O h-Ici, Darach; Jeuthe, Sarah; Dietrich, Thore; Berger, Felix; Kuehne, Titus; Kozerke, Sebastian; Messroghli, Daniel R. (The International Journal of Cardiovascular Imaging, 2015)
Current models for real time study of the effects of myocardial ischemia/reperfusion have major limitations and confounders. Confounders include the surgical stresses of a thoracotomy and abnormal physiology of an open chest. The need to reposition the animal interferes with the study of the early changes associated with ischemia. Direct comparison of pre-ischemia and post-ischemia images is then difficult. We developed a novel “closed chest” model of ischemia/reperfusion to overcome these issues. Following thoracotomy, we sutured a balloon occluder to the left coronary artery of male Sprague–Dawley rats. We used both visual inspection and ECG to assess for successful occlusion and reperfusion of the coronary artery at the time of operation by brief inflation and deflation of the balloon. The tubing was then placed under the skin and the incision closed. Following a recovery period (5–10 days), the animals underwent MRI. We performed baseline assessment of left ventricle function, and repeated LV measurement during a 15-min coronary occlusion and again during a 60-min reperfusion period following reopening of the coronary artery. The occluder was successfully placed in 40 of 44 animals. Four developed intraoperative complications; two large myocardial infarction, two terminal bleeding. Six died in the week following surgery, [four sudden deaths (presumed arrhythmic), one anterior infarction, one sepsis]. Cine-MRI demonstrated localised hypokinesia in 31 of the remaining 34 animals. LV ejection fraction (EF) was reduced from 63 ± 7 % at baseline, to 49 ± 9 % during coronary occlusion. LV EF recovered to 61 ± 2 %. The area at risk on staining of the heart was 41.9 ± 15.8 %. This method allows the effects of ischemia/reperfusion to be studied before, during, and after coronary occlusion. Ischemia can be caused while the animal is in the MRI. This new and clinically relevant small animal model is a valuable tool to study the effects of single or repeated coronary occlusion/reperfusion in real-time.